A Tiszántúl északi részéről származó diákok egyetemjárása külföldön 1292–1918 - Szögi, László (Gerundium, 2014)
THE UNIVERSITY ATTENDANCE OF STUDENTS ABROAD FROM THE NORTHERN PART OF THE TRANS TISZA REGION 1292–1918. he social and cultural history of the regions cannot be examined without exact information about the school system, the catchment area of the schools and their eiciency in a given region. his analysis includes the examination of the university attandence abroad, especially in case of countries where the university system was established with a delay, therefore university education was a valid option only at international universities. he data relating to Hungarian regions, counties, or cities can be easily obtained from this analysis. he present essay summarizies the university attending practices in the Northern part of the trans Tisza region.